2015
DOI: 10.1590/s0100-736x2015001100008
|View full text |Cite
|
Sign up to set email alerts
|

Ultrassonografia abdominal de tamanduás-bandeira (Myrmecophaga tridactyla Linnaeus, 1758) mantidos em cativeiro

Abstract: RESUMO.-A ultrassonografia é um método de imagem não invasivo e uma ferramenta importante para o diagnóstico de uma variedade de enfermidades de animais. Neste trabalho foi realizada a técnica de ultrassonografia transabdominal em cinco tamanduás-bandeira (Myrmecophaga tridactyla), dois machos e três fêmeas, pertencentes ao Zoológico da Universidade Federal de Mato Grosso e acompanhada a necrópsia de um animal morto de causas naturais. Os animais do zoológico foram anestesiados com Tiletamina e Zolazepam (Zole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 7 publications
5
10
0
6
Order By: Relevance
“…The colon is extensive, showing no clear distinction between the descending portion and the rectal, as described in domestic animals (Konig and Liebich, 2016) and the absence of sacculations in this intestinal tract was also described in this species by Souza et al (2010), as well as certified in the current work. In the three cadavers, the right and left kidneys were visualized in the mesogastric region, supporting the reports of Lopes et al (2015); however, these anatomical structures showed a more caudal projection compared to the carnivores (Getty, 1986;Lopes et al, 2015;Konig and Liebich, 2016), especially the right, differing from the pigs, which present renal symmetry (Konig;Liebich, 2016).…”
Section: Topography and Syntopy…supporting
confidence: 81%
See 4 more Smart Citations
“…The colon is extensive, showing no clear distinction between the descending portion and the rectal, as described in domestic animals (Konig and Liebich, 2016) and the absence of sacculations in this intestinal tract was also described in this species by Souza et al (2010), as well as certified in the current work. In the three cadavers, the right and left kidneys were visualized in the mesogastric region, supporting the reports of Lopes et al (2015); however, these anatomical structures showed a more caudal projection compared to the carnivores (Getty, 1986;Lopes et al, 2015;Konig and Liebich, 2016), especially the right, differing from the pigs, which present renal symmetry (Konig;Liebich, 2016).…”
Section: Topography and Syntopy…supporting
confidence: 81%
“…Still in the giant anteater, it was observed that the smaller omentum stabilizes the stomach to the hepatic lobes, according to reports of Castro et al (2010) in domestic animals and Carvalho et al (2012) in paca (Cuniculus paca). In the anteaters of this study, the hepatic localization was observed in the more cranial portion of the abdomen, with syntopy to the diaphragm muscle and stomach, as well as the spleen caudally to the stomach and with regular contours, coinciding with the sonographic findings of Lopes et al (2015).…”
Section: Topography and Syntopy…supporting
confidence: 73%
See 3 more Smart Citations